A REVIEW ON EXPLORING THE SIGNIFICANCE OF MICRONUTRIENTS IN CROP PRODUCTION (International Association of Biologicals and Computational Digest, 2023)
The essential plant nutrients for growth and development include Zinc, Iron, Boron, Molybdenum, Manganese, Copper, and Chlorine. For an agricultural product to be successfully developed proper crop nutrition is crucial. One of the most significant variables that promote crop production and development is the linked supply of micronutrients with macronutrients in sufficient levels and optimum proportions. Even though they are frequently needed in very low amounts, micronutrients are necessary for plant development. To produce a maximum number of high-quality products, vegetable production must employ micronutrients effectively. The current study has given a significant of micronutrients in crops. Zinc, Boron, Copper, Chloride, Iron, Manganese, and Molybdenum are significant micronutrients. Although Mo is particularly specific to nitrate reductase, other micronutrients are engaged in a variety of photosynthetic processes. Other micronutrients like Zn, Cu, Fe, and Mn are also connected to a variety of enzymatic activities.
Keywords: micronutrients, importance, agricultural, crop, soil